2019
DOI: 10.3389/fmicb.2019.00389
|View full text |Cite
|
Sign up to set email alerts
|

Over 2000-Fold Increased Production of the Leaderless Bacteriocin Garvicin KS by Increasing Gene Dose and Optimization of Culture Conditions

Abstract: The leaderless bacteriocin Garvicin KS (GarKS) is a potent antimicrobial, being active against a wide range of important pathogens. GarKS production by the native producer Lactococcus garvieae KS1546 is, however, relatively low (80 BU/ml) under standard laboratory growth conditions (batch culture in GM17 at 30°C). To improve the production, we systematically evaluated the impact of different media and media components on bacteriocin production. Based on the outcomes, a new medium formulation was made that incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The advantage of killing other competitors could not compensate for the metabolic cost for the production of bacteriocin ( Riley and Wertz, 2002 ). Also, the GIT might not present the optimal environmental conditions for triggering the maximum in vivo production of bacteriocin, unlike laboratory growth medium and conditions ( Telke et al, 2019 ).…”
Section: Functional Mechanisms Of Probiotics Against Campylmentioning
confidence: 99%
“…The advantage of killing other competitors could not compensate for the metabolic cost for the production of bacteriocin ( Riley and Wertz, 2002 ). Also, the GIT might not present the optimal environmental conditions for triggering the maximum in vivo production of bacteriocin, unlike laboratory growth medium and conditions ( Telke et al, 2019 ).…”
Section: Functional Mechanisms Of Probiotics Against Campylmentioning
confidence: 99%
“…Further investigation of the antimicrobial activity of isolates M1 and 17 revealed that the kinetics of production are similar to other bacteriocin producers with a maximum in the late exponential growth phase [52][53][54]. The antimicrobial compounds of isolates M1 and 17 were partially purified using ammonium sulfate precipitation and subsequent cation exchange chromatography of supernatant proteins, although the majority of the activity (approx.…”
Section: Discussionmentioning
confidence: 97%
“…The production of weissellicin Y and weissellicin M by Weissella hellenica QU 13 was nutrition-adaptive and thiamine addition decreases weissellicin Y production [155]. Pasteurized milk supplemented with tryptone significantly improved the production of garvicin KS [156].…”
Section: Iidmentioning
confidence: 98%